AKIBAT HUKUM PENGANGKATAN ANAK KEMANAKAN (Studi Penetapan Pengadilan Agama Medan Nomor 35/Pdt.P/2016/PA.Mdn) - HASUNA RAFIKA (JURNAL CIVIL LAW USU, 2018)
Adoption of children is a community need and becomes part of the family law system, because it involves the interests of individuals in the family. Therefore, child adoption institutions (adoption) which have become part of community culture, will follow the development of situations and conditions along with the level of intelligence and development of the community itself. The problem in this study, how the implementation process of child nephew appointment, how the judge’s legal considerations in the determination of the Medan Religious Court Number 35/Pdt.2016/PA.Mdn, and how the legal consequences of the appointment of child nieces based on the stipulation of the Medan Religious Court Number 35/Pdt.2016/PA.Mdn. This research is a descriptive study with a research method that is normative juridical. The data usedin this study is secondary data. Data collection techniques used in this study are literature studies. Data analysis used in this study is qualitatively. The results of this study are that the process of implementing child nephew is basically the same as the process of carrying out child adoption in general. Legal considerations of judges in examining applications for adoption of children are based on the legal basis of KHI, Law on Religious Courts, Regulation of the Minister on Religion No. 2 of 1987 and Fatwa MUI Number U-335/MUI/VI/82 dated 18 Sya’ban 1402 H. The legal consequences of child nephew adoption are the adoption of children does not cause nasab, guardian-inheritance and other legal relationships wth adoptive parents, so nasab, guardian, and heirs of adopted children remain with their biological parents. Keywords : Legal Effechts, Child Appointment, Nephew